RANCANG BANGUN WEBSITE PADA SEKOLAH MENENGAH ATAS NEGERI (studi Kasus : Sekolah Menengah Atas Negeri 6 Kota Jambi) - Faiza Rini (JURNAL AKADEMIKA)
Besides the school website to provide information to the public, the public can also provide comments, criticisms, or suggestions related to the school. So that will be an input for the development of SMP Negeri 6 Jambi. As for the other problems that often occurs is when the new admissions. In the process of activities carried out directly and manually, ie prospective students fill out the registration form, as well as knowing the result should come to the location of SMP Negeri 6 City of Edinburgh so spend a lot of time and effort in the process. To the researchers assess the need for the school website, due to the school's website can also be used as a medium in the online registration process. So that at each new school year to simplify and accelerate the process of admission of new students to graduate elementary school (SD) or Madrasah Ibtida'iyah (MI) who wish to register themselves for admission as a student at SMP Negeri 6 Jambi.